2022
DOI: 10.1021/acs.orglett.2c01827
|View full text |Cite
|
Sign up to set email alerts
|

Chan–Lam Reaction and Lewis Acid Promoted 1,3-Rearrangement of N–O Bonds to Prepare N-(2-Hydroxyaryl)pyridin-2-ones

Abstract: We describe the difunctionalization of arylboronic acids to prepare various N-(2-hydroxyaryl)pyridin-2-ones in good yields using N-hydroxypyridin-2-ones as the oxygen and nitrogen sources through a copper(II)-catalyzed Chan−Lam reaction and subsequent BF 3 -promoted selective 1,3-rearrangement of N−O bond in a one-pot procedure. Mechanistic studies reveal that the 1,3-rearrangement selectivity is controlled by the formation of the key aryloxypyridinium salt. The obtained products are easily converted to variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In 2022, Ma et al documented the synthesis of a series of N -(2-hydroxyaryl)pyridin-2-ones via the domino Chan–Lam coupling/1,3 rearrangement protocol. 67 This one-pot methodology was achieved by reacting N -hydroxypyridin-2-ones with aryl boronic acids in the presence of 20 mol% Cu(OAc) 2 , 2 equiv. pyridine in DCE at room temperature for 12 h under air, followed by the introduction of the Lewis acid catalyst BF 3 ·Et 2 O, which promoted the 1,3-rearrangement involving N–O bonds and yielded the required products in high yields at 100 °C (Scheme 64).…”
Section: Classificationmentioning
confidence: 99%
“…In 2022, Ma et al documented the synthesis of a series of N -(2-hydroxyaryl)pyridin-2-ones via the domino Chan–Lam coupling/1,3 rearrangement protocol. 67 This one-pot methodology was achieved by reacting N -hydroxypyridin-2-ones with aryl boronic acids in the presence of 20 mol% Cu(OAc) 2 , 2 equiv. pyridine in DCE at room temperature for 12 h under air, followed by the introduction of the Lewis acid catalyst BF 3 ·Et 2 O, which promoted the 1,3-rearrangement involving N–O bonds and yielded the required products in high yields at 100 °C (Scheme 64).…”
Section: Classificationmentioning
confidence: 99%
“…[8,9] In 2022, Ma and the authors reported a Chan-Lam Oarylation of N-hydroxyl-2-pyridinones combined with the Lewis acid promoted 1,3-rearrangement of NÀ O aryl moieties with heating to synthesize N-(2hydroxyaryl)pyridine-2-ols in good yields (Scheme 1-D). [10] Even so, only the [1,3]-rearrangement products were obtained. It is worth noting that the rearrangement proceeded with substituents at the 4-and 5-positions of the N-hydroxyl 2-pyridinones and the formation of the pyridinium salt was the key step in the [1,3]-rearrangement.…”
Section: Introductionmentioning
confidence: 99%
“…A seminal work has been done mainly to widen the substrate scope and enhance the reaction optimization using the introductory catalyst Cu­(OAc) 2 in the presence of a weak base (pyridine, Et 3 N etc.) . However, limited advancement has been achieved in understanding the mechanistic pathways using alternative catalytic systems by modulating the catalytic efficiency or change in reaction conditions such as ligand, solvent, or base .…”
Section: Introductionmentioning
confidence: 99%